Ancient divergence of Indian and Tibetan wolves revealed by recombination‐aware phylogenomics. Issue 24 (28th August 2021) - Hennelly, Lauren M.; Habib, Bilal; Modi, Shrushti; Rueness, Eli K.; Gaubert, Philippe; Sacks, Benjamin N.
Abstract: The grey wolf ( Canis lupus ) expanded its range across Holarctic regions during the late Pleistocene. Consequently, most grey wolves share recent (<100, 000 years ago) maternal origins corresponding to a widespread Holarctic clade. However, two deeply divergent (200, 000–700, 000 years ago) mitochondrial clades are restricted, respectively, to the Indian subcontinent and the Tibetan Plateau, where remaining wolves are endangered. No genome‐wide analysis had previously included wolves corresponding to the mitochondrial Indian clade or attempted to parse gene flow and phylogeny. We sequenced four Indian and two Tibetan wolves and included 31 additional canid genomes to resolve the phylogenomic history of grey wolves. Genomic analyses revealed Indian and Tibetan wolves to be distinct from each other and from broadly distributed wolf populations corresponding to the mitochondrial Holarctic clade. Despite gene flow, which was reflected disproportionately in high‐recombination regions of the genome, analyses revealed Indian and Tibetan wolves to be basal to Holarctic grey wolves, in agreement with the mitochondrial phylogeny. In contrast to mitochondrial DNA, however, genomic findings suggest the possibility that the Indian wolf could be basal to the Tibetan wolf, a discordance potentially reflecting selection on the mitochondrial genome. Together, these findings imply that southern regions of Asia have been important centers for grey wolf evolution and that Indian and Tibetan wolves represent evolutionary significant units (ESUs). Further study is needed to assess whether these ESUs warrant recognition as distinct species. This question is especially urgent regarding the Indian wolf, which represents one of the world's most endangered wolf populations. Abstract : see also the Perspective by Małgorzata Pilot.